2021
DOI: 10.33448/rsd-v10i3.13025
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação dos pacientes com Diabetes e Hipertensão em uma Estratégia de Saúde da Família localizada na zona rural do interior do Estado do Pará

Abstract: Objetivo: Avaliar os pacientes com diagnóstico de Diabetes Mellitus tipo 2 e Hipertensão Arterial Sistêmica em uma Estratégia de Saúde da Família (ESF) localizada na zona rural do município de Santa Bárbara do Pará, Estado do Pará, Brasil. Metodologia: Trata-se de um estudo epidemiológico, observacional, transversal e descritivo. A população estudada foi constituída pelos portadores de HAS e/ou DM II, atendidos na referida ESF, dentro do período de 1 ano. Resultados: 102 pessoas participaram do estudo. Desses,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
0
1
0
1
Order By: Relevance
“…Thus, it is possible to identify the risk of individuals to develop a cardiovascular event within 10 years (12). Systemic Arterial Hypertension (SAH) and high cholesterol levels significantly increase the probability of cardiovascular events (13,14), therefore, it becomes extremely important to calculate the CVR as a form of prevention and awareness of patients to adhere to the treatment and decrease the mortality from CVD, such as stroke and acute myocardial infarction (AMI) (15). In the WHO study (1), a higher incidence of AMI was observed among men of the 376,177 participants, between the years 1960 and 2013, in 21 regions of the world.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is possible to identify the risk of individuals to develop a cardiovascular event within 10 years (12). Systemic Arterial Hypertension (SAH) and high cholesterol levels significantly increase the probability of cardiovascular events (13,14), therefore, it becomes extremely important to calculate the CVR as a form of prevention and awareness of patients to adhere to the treatment and decrease the mortality from CVD, such as stroke and acute myocardial infarction (AMI) (15). In the WHO study (1), a higher incidence of AMI was observed among men of the 376,177 participants, between the years 1960 and 2013, in 21 regions of the world.…”
Section: Discussionmentioning
confidence: 99%
“…Dias e Médias de permanência hospitalar por HAS segundo regiões (2017 a 2020). Características sociodemográficas dos óbitos e mortalidade por 100.000 habitantes por HAS segundo regiões, de 2017 a 2020.A taxa de mortalidade por 100.000 habitantes por HAS foi mais elevada na Região Nordeste(2,6), sendo de 1,0 em Teresina e 1,6 no Piauí, respectivamente. Os resultados revelaram uma tendência de queda na taxa de mortalidade por 100 mil habitantes em 2017 (Tabela 3).…”
unclassified